Efficacy and Safety of Topical Timolol Eye Drops in the Treatment of Myopic Regression after Laser In Situ Keratomileusis: A Systematic Review and Meta-Analysis - Xiaochen Wang; Guiqiu Zhao; Jing Lin; Nan Jiang; Qian Wang; Qiang Xu (Journal of Ophthalmology)
Aims. The aim of this study was to assess the efficacy and safety of timolol in the treatment of myopic regression after laser in situ keratomileusis (LASIK). Methods. We searched MEDLINE, CENTRAL, EMBASE, China National Knowledge Infrastructure (CNKI), and Chinese Biological Medicine (CBM) from the inception to July 2015 for relevant randomized controlled trials that examined timolol therapy for myopic regression. The methodological quality of the studies included was assessed using the Revman 5.3 software. Results. We included six clinical trials involving 483 eyes in this review, including 246 eyes in treated group and 237 eyes in controlled group. We observed statistically significant improvements on the postoperative SE in the 3 months. However, the change of CCT was not statistically different between the control group and the experimental group. There were fewer cases of IOP, UDVA, and CDVA in treated group having significant difference from the controlled group. Conclusions. Topical timolol could be an effective treatment for reduction of myopic regression especially the spherical errors after myopic LASIK. Further RCTs with larger sample sizes for these trials are warranted to determine the efficacy and limitation for myopic regression after LASIK.